La ricalibratura delle policy sull’ICT nella scuola italiana: “lezioni” dalla DaD - Carbone, Domenico; Calvi, Cristina; Favretto, Anna Rosa (Cambio (Firenze), 2024)
The article proposes an analysis of digital education policies in Italy starting from the distance learning, experienced by the Italian school system during the Covid-19 pandemic. Starting from the numerous empirical studies carried out on this topic, the article aims to highlight the outcomes of distance learning in relation to three aspects on which school digitisation policies, in Italy as in the rest of Europe, have focused their objectives in the last twenty years: the improvement of learning levels, the development of digital skills and the increase in school inclusion. Through a bottom-up approach that therefore places the experiences of students and teachers at the centre of the analysis, the article intends to present a comprehensive reflection on the outcomes of digital policies in schools, proposing possible strategies for recalibration.